Single-Stranded DNA Curtains for Studying Homologous Recombination - Ma, C.J. (Methods Enzymol, 2016)
Homologous recombination is an important pathway involved in the repair of double-stranded DNA breaks. Genetic studies form the foundation of our knowledge on homologous recombination. Significant progress has also been made toward understanding the biochemical and biophysical properties of the proteins, complexes, and reaction intermediates involved in this essential DNA repair pathway. However, heterogeneous or transient recombination intermediates remain extremely difficult to assess through traditional ensemble methods, leaving an incomplete mechanistic picture of many steps that take place during homologous recombination. To help overcome some of these limitations, we have established DNA curtain methodologies as an experimental platform for studying homologous DNA recombination in real-time at the single-molecule level. Here, we present a detailed overview describing the preparation and use of single-stranded DNA curtains in applications related to the study of homologous DNA recombination with emphasis on recent work related to the study of the eukaryotic recombinase Rad51.